Sialyl LewisX/A and Cytokeratin Crosstalk in Triple Negative Breast Cancer - Pascoal, Carlota (2023)
project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy—i4HB. Publisher Copyright: © 2023 by the authors.